Design and optimization of electromagnetic transducer for aeroelastic energy harvesting - Filho, Marcelo Jorge [UNESP]; De Vasconcellos, Rui Marcos Grombone [UNESP]; Ferreira, Andre Alves [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2019)
The energy harvesting from oscillations of structures immersed in a moving fluid has received attention from the scientific community in recent years. Particularly, oscillations resulting from dynamically stable non-linear effects, induced or not, favor this harvesting. There are numerous applications for the energy harvesting of the oscillation of aeronautical structures, among them, wireless sensors powering and other electronic devices. In addition to energy utilization, another beneficial effect, as a result of the conversion of some of this energy, is the decrease in the amplitude of oscillation, resulting in less damage to the structure. The proposed energy harvest uses as a transducer an electromagnetic induction system that will be optimized in this work to later be coupled to the structure of a typical aeroelastic section, with one degree of freedom in torsion exposed to the fluid flow.
Keywords: Aeroelastic System; Eletromagnetic Simulation; Eletromagnetic transducers; Energy Harvesting; Optimization